Outcomes and Risk Factors of Systolic Pulmonary Artery Pressure Progression in Patients with Systemic Rheumatic Diseases: Follow-up Results from a Korean Registry - Mi Ryoung SEO; Jina YEO; Hee Jung RYU; Hyo-jin CHOI; Kwang-pil KO; Han Joo BAEK (Archives of Rheumatology, 2020)
Objectives: This study aims to investigate the outcomes and risk factors associated with the progression of systolic pulmonary artery pressure (sPAP) in patients with systemic rheumatic diseases. Patients and methods: A total of 532 patients (73 males, 459 females; median age 49 years; interquartile range (IQR), 36 to 62 years) registered with the Registry of Pulmonary Hypertension Associated with Rheumatic Diseases were included. Mortality curves were constructed using the Kaplan- Meier method and comparisons were performed using the log-rank test. A paired t-test was performed to evaluate the patients with markedly elevated sPAP between baseline and follow-up. Results: The average follow-up duration was 31 months (IQR, 9 to 60 months). Of the patients, 196 had follow-up echocardiographs at least one year later. We defined the sPAP over 60 mmHg as markedly elevated. Patients in the increased sPAP above 60 mmHg at follow-up and persistently markedly elevated sPAP were associated with worse outcomes in all-cause mortality and pulmonary arterial hypertension-related mortality (p<0.001). In patients with systemic sclerosis, the majority of patients remained static within their pressure group or rose progressively: the patients with markedly elevated sPAP at follow-up were higher than those at baseline (32% versus 15%, p<0.01). In patients with mixed connective tissue disease (MCTD) or rheumatoid arthritis (RA), the majority of patients remained static within their pressure group or gradually improved: the patients with markedly elevated sPAP at follow-up were lower than those at baseline (RA=14% versus 29%, MCTD=5% versus 16%, p<0.05). Conclusion: Persistently high sPAP or increase of sPAP over 60 mmHg at follow-up was associated with increased mortality. There were some differences in the progression of sPAP according to the underlying rheumatic diseases.